In vitro and in vivo evaluation of [123I]-VEGF165 as a potential tumor marker. - Cornelissen, B; Oltenfreiter, R; Kersemans, V; Staelens, L; Frankenne, F; Foidart, J; Slegers, G (2005)
One of the research challenges in oncology is to develop new biochemical methods for noninvasive tumor therapy evaluation to determine whether the chemotherapeutics is effective. Vascular endothelial growth factor (VEGF) was labeled with radioiodine and evaluated in vitro as well as in vivo, using A2058, a melanoma cell line overexpressing VEGFR-1 and -2. Saturation binding analysis with [(125)I]-VEGF resulted in a K(d) of 0.1 nM. Internalization assays indicate the preserved ligand induced internalization and metabolization of the tracer. Biodistribution studies with [(123)I]-VEGF in wild type and A2058 tumor-bearing athymic mice showed low background activity and a tumor to reference tissue ratio of maximum 6.12. These results suggest that [(123)I]-VEGF is a potentially suitable tracer for tumor therapy evaluation.